A bibliometric analysis of the 100 most cited articles describing SARS-CoV-2 variants - Yahui Zhang; Meijing Feng; Yongmei He; Fangming Liu; Rui Ma (Frontiers Media S.A., 2022)
BackgroundThe emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with mutations in the spike protein has risen concerns about the efficacy of infection- or vaccine-induced antibodies and has posed a serious threat to global public health, education, travel and economy. Few studies have described the detailed characterizations of highly cited articles on SARS-CoV-2 variants.ObjectiveTo identify and characterize the 100 most-cited articles in SARS-CoV-2 variants research.Design and methodsArticles published recently were extracted from the web of science core collection database using a query based on MeSH terms and topics of SARS-CoV-2 and variants. Characteristics of the 100 most-cited articles were analyzed via the following parameters: publication number over year, number of citations, type of articles, authors, journal, journal impact factor, country, and topics covered in articles. In addition, clinical trials in these articles were also analyzed.ResultsThe majority of articles (66%) were published in 2021. Number of citations of the 100 most cited articles ranged from 1720 to 75 (median: 178.5). Mutations in the S protein such as D614G mutation and the B.1.1.7 (UK) and B.1.351 (South Africa) were the dominant variants in the 100 most cited articles. The United States, the United Kingdom, and South Africa had the strongest collaboration in the contribution of publication. Science, Cell, Nature and New England Journal of Medicine were mostly cited and the main direction in these top journals were vaccine neutralizing tests and efficacy evaluation studies. Response of antibody neutralization tests against variants was always weakened due to the presence of variants but the results of clinical trials were encouraging. Genomics information, spike protein structure confirmation and neutralization studies evaluating antibody resistance were highly represented in the 100 most cited articles in SARS-CoV-2 variants literature.Conclusions and relevanceAltogether, genomic information, epidemiology, immune neutralization, and vaccine efficacy studies of COVID-19 variants are the main research orientations in these articles and relevant results have been published in influential journals. Given the continuous evolution of the SARS-CoV-2 and the constant development in our understanding of the impact of variants, current working strategies and measures may be periodically adjusted.